China-Pakistan Economic Corridor, logistics developments and economic growth in Pakistan - Zunaira Khadim; Irem Batool; Muhammad Bilal Lodhi (Logistics, 2021)
The study aims to analyze the impact of China-Pakistan Economic Corridor (CPEC) logistics-related developments on economic growth in Pakistan. The study defined a Cobb-Douglas type of research framework in which the country's real income level relates to four factor inputs, e.g., employed labor force, logistics development, financial development, and energy consumption in an economy. The study utilized the time series data set for the period 1972-2018. To estimate the long run relationship and short run adjustment mechanism, the study used Johansen's method of co-integration and error correction model. Estimated results showed that the country's logistics developments have a significant positive impact on economic growth in both the long run and the short run. It implies that China-Pakistan collaborative efforts for logistics developments will have a strong positive impact on economic growth in Pakistan.
Keywords: 650; China-Pakistan Economic Corridor developments; logistics developments; economic growth; Pakistan